2012
DOI: 10.1002/mrm.24177
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of T1‐relaxation in ex vivo prostate tissue at 132 μT

Abstract: The proton T 1 was measured at 132 mT in ex vivo prostate tissue specimens from radical prostatectomies of 35 patients with prostate cancer. Each patient provided two specimens. The NMR and MRI measurements involved proton repolarization, a field of typically 150 mT and detection of the 5.6-kHz signal with a superconducting quantum interference device. Values of T 1 varied from 41 to 86 ms. Subsequently, the percentages of tissue types were determined histologically. The theoretical image contrast is quantifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 24 publications
0
46
0
Order By: Relevance
“…To understand how far our configuration was from the one maximizing the energy transfer from the double-D to the MS, the optimal input coil inductance L iopt and the optimal gain G opt Φ were estimated using Eqs. (5) and (6). We obtained L iopt ≈ 11.4 µH and G opt Φ ≈ 5.65 × 10 −2 .…”
Section: Coupling Between the Double-d And The Mixed Sensormentioning
confidence: 67%
See 1 more Smart Citation
“…To understand how far our configuration was from the one maximizing the energy transfer from the double-D to the MS, the optimal input coil inductance L iopt and the optimal gain G opt Φ were estimated using Eqs. (5) and (6). We obtained L iopt ≈ 11.4 µH and G opt Φ ≈ 5.65 × 10 −2 .…”
Section: Coupling Between the Double-d And The Mixed Sensormentioning
confidence: 67%
“…However, during the last decade, some advantages of working at very low static fields (below 100 mT) have been suggested [1,2]. Such low-field NMR apparatuses, as compared to conventional high-field scanners, provide a higher frequency resolution of NMR lines [3,4], are less prone to susceptibility artefacts, require only moderate relative homogeneity of the static field [5] and, notably, the possibility of exploiting enhanced T1 contrast at low-field strengths, e.g., for the detection of tumours, has been recently suggested [6]. Finally, low-field NMR apparatuses can be integrated with other medical modalities such as magnetoencephalography (MEG) [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperpolarization techniques, which significantly enhance spin population difference, were introduced in LF/ULF nuclear magnetic resonance (NMR) and MRI systems to obtain stronger SNR [5][6][7]. Some potential applications of ULF MRI have been demonstrated compared with high field MRI, e.g., enhanced contrast between cancerous and surrounding tissues [8,9], the possibility of imaging in the presence of metallic objects [10], the hybrid biomagnetic imaging of MRI and magnetoencephalography (MEG) [11,12] and the feasibility of neuronal current imaging [13][14][15]. Most of these advantages were achieved in a magnetically shielded room (MSR), which is costly, or in a shielded room made from aluminum a few millimeters thick.…”
Section: Introductionmentioning
confidence: 99%
“…The discrimination using T 1 contrast may be easier at ultra-low fields (ULF) in the microtesla range: Recently it was shown that biopsies of prostate-cancer tissue have significantly shorter T 1 relaxation times than healthy prostate tissue in fields well below one millitesla [3]. Apparently, T 1 relaxation times of these tissue samples exhibit a dispersion that changes significantly towards lower Larmor frequencies, a behavior that facilitates the observation of contrast by ULF MRI.…”
Section: Introductionmentioning
confidence: 99%
“…Then, we searched for the optimal field again. We increased the number of field steps and repeated the optimization until we found no significant improvements in the value of (3).…”
mentioning
confidence: 99%